Induction and inhibition of human cytochrome P4501 by oxygenated polycyclic aromatic hydrocarbons. Issue 3 (15th March 2016) - Wincent, Emma; Le Bihanic, Florane; Dreij, Kristian
Abstract : Our data represent the first demonstration that oxy-PAHs can be potent inhibitors of CYP1 expression and function. Abstract : Oxygenated polycyclic aromatic hydrocarbons (oxy-PAHs) are found in the environment together with PAHs. However, less is known concerning their biological activity including their impact on aryl hydrocarbon receptor (AHR) signalling and the subsequent modulation of the cytochrome P450 monooxygenases (CYP). In this study, the effects of 15 environmentally relevant oxy-PAHs on the induction and activity of the CYP1 enzymes were determined in vitro by measuring gene expression levels and enzyme activity. We found that nine of the tested oxy-PAHs significantly induced CYP1A1 and CYP1B1 gene expression in human keratinocytes (HaCaT cells) while only five of these also were potent inducers of CYP1-dependent ethoxyresorufin- O -deethylase (EROD) activity suggesting that some of the oxy-PAHs are both activators of AHR signalling and inhibitors of CYP1 function. Using a recombinant human CYP1A1 enzyme we showed that eleven of the oxy-PAHs potently inhibited enzyme activity with benz[ a ]anthracene-7, 12-quinone (7, 12-BAQ) and benzo[ a ]fluorenone (BFLO) being the most potent inhibitors (IC50 = 0.037 and 0.061 μM, respectively). We further exposed HaCaT cells to binary mixtures of oxy-PAHs and the model AHR agonist 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) to investigate potential interaction effects. The results showed that oxy-PAHs can interfere with the TCDD-mediated effects leading to reduced CYP1A1 and 1B1 expression and EROD activity. These data represent the first demonstration that oxy-PAHs can be potent inhibitors of CYP1 expression and function and make important contributions towards understanding the mechanisms through which oxy-PAHs can contribute to the overall risk of polycyclic aromatic compounds.